TIPE KEPRIBADIAN TOKOH UTAMA PADA NOVEL “INTROVER” KARYA M.F. HAZIM - Asngadi Rofiq; Muhammad Afifuddin (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2020)
The author tries to analyze the personality of the main characters using the study of literary psychology, whether the main character is more melancholic or pblegmatic. M.F. Hazim in his novel "Introver" tells the story of the world intover. Reading it, we are invited to explore in the mind and soul of an introver who is always nervous, restless, and upset; also the inner conflict that torments him, and how he finds "friends" to fill his loneliness and make his life more meaningful. The author wants to know more clearly what exactly the lives of introverts are in their daily lives. This research is directed to one main problem, namely "What is the personality type of the main character introver in the" Introver "novel by M.F. Hazim ". This research uses descriptive qualitative method with heuristic and hermeneutic reading techniques in order to understand and reveal "something" contained in literary works. The results of the research that have been carried out are in accordance with the research hypothesis, namely the main character Nawawi has an introvert personality type in the novel "Introver" by M.F. Hajim. Researchers found 42 quotes stating that Nawawi has an introverted personality type. Of the 42 quotes that have been found, 28 quotes state that Nawawi has a melancholic personality type and 14 quotes state that Nawawi has a phlegmatic personality type.